Use completing the square to solve x^2+6x=13
![Use completing the square to solve x26x13 class=](https://us-static.z-dn.net/files/db9/d20b6fef0b8af97de1dc7245ba2abe35.jpg)
Answer:
x = -3 +/- square root(22)
Step-by-step explanation:
x = -b +/- square root(b^2 - 4ac) / 2a
ax^2 + bx + c = 0
these are both the quadratic formula but one is solved for the x and another for 0
a= 1
b= 6
c = -13
x= -6 +/- square root( 6^2 - 4(1)(13)) / 2(1)
x = -6 +/- sqrt( 36 + 52) / 2
x= -6 +/- sqrt (88) / 2
sqrt of 88 = 2 x sqrt (22)
divide 2 on each
x= -3 +/- sqrt (22)